Synthesis and properties of new (−)-menthol-derived chiral liquid crystal compounds with alkyl or alkoxy terminal groups. Issue 3 (19th February 2017) - Jia, Ying-Gang; Luo, Cong-Cong; Zhu, Zhao-Xia; Hu, Jian-She
ABSTRACT: Two series of chiral mesogenic compounds derived from (−)-menthol with varying length of alkyl or alkoxy terminal groups respectively were designed and synthesised. Their chemical structures were characterised by FT-IR and 1 H-NMR spectra. The thermal properties and optical textures were investigated by differential scanning calorimetry and polarising optical microscopy. Bragg selective reflection spectra of the compounds with the alkoxy chain in the N* phase were measured by ultraviolet/visible spectrometer. The results showed that the alkyl series homologues melt directly to the isotropic phase on heating and display cubic blue phase and focal conic textures of chiral nematic phase on cooling, whereas the alkoxy series displayed oily streak textures with iridescent colours on heating, and platelet textures of blue phase and focal conic textures were observed on cooling cycles. The chain structure and length of the terminal groups have profound influence on the isotropic temperature and a large odd–even effect is observed for the compounds. The selective reflection colours of alkoxy series shifted to longer wavelength with the increasing of temperature. GRAPHICAL ABSTRACT: